If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(39x-11)=2(17x+6)
We move all terms to the left:
2(39x-11)-(2(17x+6))=0
We multiply parentheses
78x-(2(17x+6))-22=0
We calculate terms in parentheses: -(2(17x+6)), so:We get rid of parentheses
2(17x+6)
We multiply parentheses
34x+12
Back to the equation:
-(34x+12)
78x-34x-12-22=0
We add all the numbers together, and all the variables
44x-34=0
We move all terms containing x to the left, all other terms to the right
44x=34
x=34/44
x=17/22
| 39x-11=17+6 | | 39x-11=2(17x+6) | | -3/8-7x=-149/24 | | 2(39x-11)=17x+6 | | 9x+1=-1x+19 | | 14^-9x=3^x-5 | | 5x+5=2x+3+x | | -18x+14-17x=4x | | -15x+122=-8x+66 | | -8x-20=-5x-11 | | 2x-21=x-14 | | 10x+19=15x+29 | | -24x+99=-16x+51 | | -79=-1-6n | | 9p-9=18 | | 3p-6=-54 | | Y=2.3x+6 | | -12=(f-6) | | x²+8+15=63 | | 20+50x=10+5x | | 2n+1=5n= | | 12x+20=19x+18 | | -1.14x+0.26=-10 | | -9/5x-2=-20 | | 0.47x+1.24=5 | | 9/2x+5=-31 | | 6w+4=1 | | 63=7(1+4b | | 35x-25=17 | | 3/2(x-4)+9=3 | | 4(x+1)+12=-8 | | 19.75+3x=49.75 |